Impacts of sovereign risk premium on bank profitability : evidence from euro erea - Nguyen, Sang (2021)
This study examines the impacts of the sovereign risk premium on bank profitability of 154 Eurozone banks between 2005 and 2019, using the differenced generalized method of moments. Contrary to previous literature results, banks' net interest margin actually benefits from the low and negative rate policy. Meanwhile, the overall profitability measures experience contraction due to the same effect. This puzzle can be explained by the shift towards the low-cost wholesale-based funding of banks in the Euro area. Simultaneously, such banks set aside more loan loss provisions because of the increment in overall risk of the economy. These results open up new research direction on how much interbank funding has been raised to facilitate new loans and how much of it has been for liquidity requirements. In the same manner, further research should be carried to see whether the benefits from the low-priced interbank markets funding are offset by extra costs caused by a higher ratio of loan loss provisions.